2020
DOI: 10.1007/s13300-020-00910-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Once-Weekly Dulaglutide in Elderly Chinese Patients with Type 2 Diabetes: A Post Hoc Analysis of AWARD-CHN Studies

Abstract: Introduction: This analysis evaluated the efficacy and safety of dulaglutide in Chinese patients with type 2 diabetes (T2D) aged C 60 and \ 60 years. Methods: This post hoc analysis included patients with T2D enrolled in two phase 3 clinical trials AWARD-CHN1 (NCT01644500) and AWARD-CHN2 (NCT01648582) of dulaglutide 0.75 and 1.5 mg. Patients were Digital Features To view digital features for this article go to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 24 publications
(35 reference statements)
2
5
0
Order By: Relevance
“…However, the safety outcomes reported by these prior studies mainly included hypoglycemia and gastrointestinal adverse events, and there are limited data on the pancreatic safety of GLP-1 RAs in elderly patients. The present study addresses this knowledge gap and provides evidence that the pancreatic safety profile of dulaglutide is similar in Chinese patients with T2DM aged \ 60 and C 60 years and, together with previous reports, suggests dulaglutide is a safe and effective treatment option for elderly patients with T2DM [34,35]. The results of this analysis also showed no association between patient sex and pancreatic safety of dulaglutide.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, the safety outcomes reported by these prior studies mainly included hypoglycemia and gastrointestinal adverse events, and there are limited data on the pancreatic safety of GLP-1 RAs in elderly patients. The present study addresses this knowledge gap and provides evidence that the pancreatic safety profile of dulaglutide is similar in Chinese patients with T2DM aged \ 60 and C 60 years and, together with previous reports, suggests dulaglutide is a safe and effective treatment option for elderly patients with T2DM [34,35]. The results of this analysis also showed no association between patient sex and pancreatic safety of dulaglutide.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, an appreciable increase in the incidence of, and risk of mortality from, acute pancreatitis has been observed among elderly [33]. Previous studies have shown that the efficacy and safety of dulaglutide is similar across patient age groups [34,35]. Furthermore, liraglutide and exenatide have been shown to be well tolerated regardless of patient age [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Discontinuations of study drug as a result of any AE or specifically because of nausea, vomiting or diarrhoea were not significantly different among older versus younger patients, further supporting the conclusion that overall and GI tolerability of dulaglutide across the dose range studied in AWARD‐11 are similar between age groups, consistent with prior studies with lower doses of dulaglutide. 9 , 12 The dulaglutide safety profile related to SAEs was also comparable between age groups across all doses. The incidence of SAEs was not dose‐related in either age subgroup.…”
Section: Discussionmentioning
confidence: 83%
“…The incidence of total (including severe) hypoglycaemia and documented symptomatic hypoglycaemia was low, with no significant evidence of a differential treatment effect between age groups, consistent with prior studies with lower doses of dulaglutide. 9 , 12 These results are particularly reassuring in the treatment of elderly patients with T2D because of their increased risk of hypoglycaemia and complications associated with hypoglycaemia, including falls, fractures, depression, cardiac arrhythmias and other cardiac events, cognitive impairment, dementia, and an overall reduced quality of life. 27 , 28 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation